Comparison of Topsis, Moora, and Waspas Methods In Website-Based Employee Performance Assessment (Case Study: Tirta Argapura Regional Public Company Of Drinking Water, Probolinggo Regency): Perbandingan Metode TOPSIS, MOORA, dan WASPAS Pada Penilaian Kinerja Karyawan Berbasis Website (Studi Kasus : Perusahaan Umum Daerah Air Minum Tirta Argapura Kabupaten Probolinggo) - Kusuma, Erlangga Dwi; Sisephaputra, Bonda (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
This research aims to design and develop a web-based employee performance assessment information system at the Regional Water Supply Company Tirta Argapura, Probolinggo Regency. It employs the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA), and Weight Aggregated Sum Product Assessment (WASPAS) methods for performance evaluation. A comparison among these methods is conducted using sensitivity analysis to determine the best-performing method. The system development follows the Rapid Application Development (RAD) methodology, involving requirement planning, user design, construction, and cutover phases. Blackbox and Whitebox testing techniques are employed to ensure the system's functionality and correctness after development. The research findings indicate that the rankings from TOPSIS, MOORA, and WASPAS align closely with manual calculations used as benchmarks during the method implementation for the employee assessment website design. Sensitivity testing reveals sensitivity values of 0.081 for TOPSIS, -5.542 for MOORA, and -5.964 for WASPAS. Consequently, WASPAS shows high sensitivity while TOPSIS remains stable against changes in criteria weights, leading to the conclusion that TOPSIS is the optimal method for assessing employee performance at the Regional Water Supply Company Tirta Argapura, Probolinggo Regency.